Role of platelet-rich plasma in combination with alloplastic bone substitute in regeneration of osseous defects - Indrajeet Singh; Hemant Gupta; R Pradhan; VP Sinha; Sumit Gupta (Elsevier, 2011)
ABSTRACT: Introduction: Bone grafts are frequently used for the treatment of bone defects, but can cause postoperative complications, and sometimes a sufficient quantity of bone is not available. Hence, synthetic biomaterials have been used as an alternative to autogenous bone grafts. Recent clinical reports suggest that application of autologous blood plasma enriched with platelets can enhance the formation of new bone. There are very few in vitro or in vivo studies published on the efficiency of platelet-rich plasma (PRP). The objective of this study was to evaluate the alloplastic bone substitute for its osteogenic potential with or without PRP. Materials and Methods: Twenty-three patients with periapical bony defects were selected for this study. Clinical parameters such as pain visual analog scale (VAS), swelling, infection, graft migration, rejection, radiographical interpretations at regular interval and scintigraphic evaluation were done to evaluate osteogenic potential of alloplastic bone substitute with or without PRP. Results: The highest acceleration in bone formation was observed in groups where alloplastic bone substitute was used with PRP. There were no statistically significant differences between the two groups regarding other outcome variables throughout the postoperative period. Conclusion: Addition of PRP significantly accelerates vascularization of the graft, improves soft tissue healing, reduces postoperative morbidity and enhances bone regeneration.